Modelo de gerenciamento de estoques de peças de reposição para empresas de transporte urbano de passageiros - Fernandes, Roberto Klecius Mendonça (2010)
This work searches to offer a model to improve spare parts stock management for companies of urban passenger transport by bus, with the consequent progress in their maintenance management. Also known as MRO items (Maintenance, Repair and Operations), these spare parts, according their consumption and demand features, cost, criticity to operation, lead-time, quantity of suppliers, among other parameters, shouldn´t have managed their inventory like normal production items (work in process e final products), that because their features, are managed by more predictable models based, for example, in economic order quantity. In the case specifically of companies of urban passenger transport by bus, items MRO have significant importance in their assets and a bad management of these inventories can cause serious losses to company, leading it even bankrupticy business, in more severe situations which missing spare part provokes vehicles shutdown indefinitely. Given slight attention to the issue, which translates in little literature available about it when compared to that literature about normal items stocks, and due the fact that MRO items be critical to bus urban transport of passengers companies´, it is necessary, so, deepen in this theme searching to give technical and scientific subsidies to companies that work, in many times, empirically, with these so decisive inputs to their business. As a typical portfolio problem, in which there are n items, separated into critical and noncritical, while competing for the same resource, it was developed a new algorithm to aid in a better inventory management of spare parts used only in corrective maintenance (whose failures are unpredictable and random), by analyzing the cost-benefit ratio, which compares the level of service versus cost of each item. The model was tested in a company of urban passenger transport by bus from the city of Natal, who anonymously provided their real data to application in this work